Method for brazing graphite / copper dissimilar material by using diamond particle reinforced AgCuInTi composite brazing filler metal

By using diamond particles to enhance AgCuInTi composite solder, the joint stress problem caused by the difference in thermal expansion coefficient of graphite and copper materials is solved, and reliable connection and high thermal conductivity of graphite/copper heterogeneous materials are achieved.

CN119566623AActive Publication Date: 2025-03-07HARBIN INST OF TECH
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202411870222.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-07
Estimated Expiration
2044-12-18

AI Technical Summary

Technical Problem

Due to the large differences in thermal expansion coefficients of graphite and copper, the use of direct brazing will create extremely severe residual stress in the joint, resulting in the inability to obtain a reliable joint.

Method used

Diamond particles reinforced AgCuInTi composite brazing material is used as the intermediate layer, and graphite and copper materials are connected through brazing technology, and the thermal expansion coefficient of the brazing material layer is used to reduce the stress in the joint.

Benefits of technology

Reliable connection of graphite/copper heterogeneous materials is achieved, the strength and thermal conductivity of the joint are improved, and the stress problems caused by thermal expansion mismatch are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119566623A_ABST
    Figure CN119566623A_ABST
Patent Text Reader

Abstract

The invention discloses a method for brazing a graphite / copper dissimilar material by using diamond particle reinforced AgCuInTi composite brazing filler metal, and relates to a method for brazing the graphite / copper dissimilar material. The invention aims to solve the technical problem that a reliable joint cannot be obtained due to great residual stress generated in the joint by using a direct brazing mode because the difference between the thermal expansion coefficients of graphite and copper is great. The AgCuInTi brazing filler metal and the diamond particles are evenly mixed in a ball milling mode to prepare the composite brazing filler metal, and the composite brazing filler metal is used for brazing graphite / copper dissimilar materials under vacuum. According to the method, reliable connection of the graphite / copper dissimilar materials is successfully achieved, the room-temperature shear strength of the connector can reach 30 MPa, the problem that the residual stress in the dissimilar material connector is large is solved, and application of the graphite / copper dissimilar material component in the fields of nuclear power, radiation protection and the like can be achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for brazing graphite / copper dissimilar materials. Background Art

[0002] The discovery and application of nuclear energy is one of the greatest scientific and technological achievements of the 20th century. Many devices and equipment that are vital to human development have been developed around nuclear energy, such as controlled nuclear fusion devices and particle accelerators. While these devices and equipment bring benefits to mankind, they are also accompanied by the generation of a large amount of radiation, which can cause serious damage to the human body and the environment. Radiation protection has also become a top priority in the operation of nuclear energy equipment and equipment. In addition, a large amount of heat is often generated during the radiation process, which requires radiation protection materials to have good heat transfer properties.

[0003] Carbon materials have been receiving much attention as high thermal conductivity materials with great development potential due to their excellent properties such as high thermal conductivity, low density, low thermal expansion coefficient and high temperature resistance. Among them, graphite, in addition to the above advantages, also has special thermal properties, light weight, radiation resistance, excellent thermal stability and other performance advantages, and is an ideal absorber material. However, graphite itself is brittle and has low strength, and is prone to breakage when used alone. Copper, as a traditional metal thermal management material, has a thermal conductivity of up to 400W / m·K. In addition, copper has good strength and processing properties. By connecting graphite materials with high thermal conductivity and radiation resistance with copper, heat spreaders, radiation heat exchangers, beam catchers and other components with good comprehensive performance can be prepared. At present, non-metallurgical bonding methods such as bonding are often used in the connection between graphite and copper. Although this type of connection method is simple and easy, it often cannot achieve high strength for the bonding of workpieces, and the adhesive is prone to failure in high temperature environments. In addition, the thermal conductivity of commonly used thermal conductive adhesives is very poor (0.4-10W / m·K), which greatly weakens the thermal conductivity of carbon materials. In addition, some researchers use direct brazing to connect graphite and copper. Compared with non-metallurgical bonding, direct brazing can give full play to the thermal conductivity of high thermal conductivity graphite, while preventing the workpiece from failing in a high temperature environment and extending the service life of the workpiece. However, due to the large difference in the thermal expansion coefficients of graphite and copper, the use of direct brazing will produce great residual stress in the joint, resulting in the inability to obtain a reliable joint. Therefore, it is of great significance to develop a composite brazing material suitable for graphite / copper dissimilar material connection to alleviate the residual stress problem in the joint, thereby achieving metallurgical connection between the two, which is of great significance to obtain a reliable and highly thermally conductive graphite / copper dissimilar material joint component. Summary of the invention

[0004] The present invention aims to solve the technical problem that due to the great difference in thermal expansion coefficients between graphite and copper, the direct brazing method will generate great residual stress in the joint, thereby making it impossible to obtain a reliable joint, and provide a method for brazing graphite / copper dissimilar materials using diamond particle reinforced AgCuInTi composite brazing filler metal.

[0005] The method for brazing graphite / copper dissimilar materials with diamond particle reinforced AgCuInTi composite brazing filler metal of the present invention is carried out by the following steps:

[0006] 1. Preparation of composite solder: AgCuInTi solder powder and diamond particles are preliminarily mixed in an agate mortar, and then the mixed powder is placed in a ball mill, and ball milled at a low speed using a ball mill until fully mixed and uniform, to obtain composite solder powder;

[0007] The volume fraction of diamond particles in the composite solder is 5% to 15%;

[0008] 2. Pretreatment of graphite and copper base materials;

[0009] 3. Assembling the parts to be welded: mixing the composite solder powder prepared in step 1 with a binder to form a paste solder, applying the paste solder to the surface of the copper base material to be welded by screen printing, and then placing the surface of the graphite base material to be welded on the paste solder, thereby assembling a graphite / diamond particle reinforced AgCuInTi composite solder / copper part to be welded;

[0010] 4. Brazing: Place the parts to be welded in step 3 into a graphite mold, and then load them into a vacuum furnace. First, heat them to 300℃~310℃ and keep them warm for 30min~35min to remove the binder, then heat them to 680℃, and then heat them to the brazing temperature of 680℃~800℃ and keep them warm for 5min~20min; finally, cool them to 300℃, and then cool them to room temperature with the furnace to complete the entire brazing process. The entire brazing process is carried out under vacuum.

[0011] Compared with the prior art, the present invention provides a diamond particle reinforced composite solder that is easy to prepare and low-cost, and realizes the connection of graphite / copper under low-temperature vacuum conditions. The specific beneficial effects are as follows:

[0012] 1. The composite solder provided by the present invention is used for the method of connecting graphite / copper dissimilar materials, wherein the composite solder reinforced with diamond particles is used as the intermediate layer, and the graphite / copper dissimilar materials are connected by direct brazing, wherein the AgCuInTi composite solder has the properties of good fluidity, low melting point and excellent wetting with the parent material, and at the same time, the connection layer has few defects and the joint reliability is high;

[0013] 2. AgCuInTi solder itself is one of the solders with the best heat transfer performance (thermal conductivity is about 100-180W / m·K), and diamond is one of the materials with the highest thermal conductivity in nature (thermal conductivity is about 1000-2000W / m·K). The addition of diamond particles can further improve the heat transfer performance of the solder; in addition, diamond also has the advantages of low expansion coefficient, high strength, and low density. The addition of diamond particle reinforcement phase can also reduce the thermal expansion coefficient of the solder layer, thereby forming a buffer zone between the two base materials, which greatly alleviates the problem of excessive stress in the joint caused by the mismatch of the thermal expansion coefficient of the base materials;

[0014] 3. In the connection process of the present invention, the brazing material interacts with the base material. After the surface of the graphite base material contacts the composite brazing material, the composite brazing material infiltrates into the pores of the graphite base material to form an infiltration layer similar to the "pinning" effect, which is beneficial to the improvement of the joint strength. The brazing material reacts with the graphite base material to form a TiC reaction layer, and a diffusion layer is formed on the copper base material side. Finally, the maximum room temperature shear strength of the joint obtained by heat preservation at 740°C for 10 minutes is about 30MPa. Therefore, the present invention uses diamond particle reinforced AgCuInTi composite brazing material as an intermediate layer for the connection of graphite / copper dissimilar materials, which can achieve good wetting and interface bonding of the base material, thereby realizing the forming and manufacturing of large-sized and complex-shaped structural parts. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 This is the SEM image of the composite solder powder prepared by ball milling in step 1 of experiment 1;

[0016] Figure 2 This is the EDS image of the C element in the composite solder powder prepared by ball milling in step 1 of experiment 1;

[0017] Figure 3 This is the SEM image of the graphite / copper dissimilar material joint prepared in comparative test 1;

[0018] Figure 4 XRD pattern of graphite / copper dissimilar material joint prepared in comparative experiment 1;

[0019] Figure 5 This is the EDS image of the graphite / copper dissimilar material joint prepared in comparative test 1, where the scale is 2.5 μm;

[0020] Figure 6 This is the SEM image of the graphite / copper dissimilar material joint prepared in experiment 2. DETAILED DESCRIPTION

[0021] Specific implementation method 1: This implementation method is a method for brazing graphite / copper dissimilar materials using diamond particle reinforced AgCuInTi composite brazing filler metal, which is specifically carried out in the following steps:

[0022] 1. Preparation of composite solder: AgCuInTi solder powder and diamond particles are preliminarily mixed in an agate mortar, and then the mixed powder is placed in a ball mill, and ball milled at a low speed using a ball mill until fully mixed and uniform, to obtain composite solder powder;

[0023] The volume fraction of diamond particles in the composite solder is 5% to 15%;

[0024] 2. Pretreatment of graphite and copper base materials;

[0025] 3. Assembling the parts to be welded: mixing the composite solder powder prepared in step 1 with a binder to form a paste solder, applying the paste solder to the surface of the copper base material to be welded by screen printing, and then placing the surface of the graphite base material to be welded on the paste solder, thereby assembling a graphite / diamond particle reinforced AgCuInTi composite solder / copper part to be welded;

[0026] 4. Brazing: Place the parts to be welded in step 3 into a graphite mold, and then load them into a vacuum furnace. First, heat them to 300℃~310℃ and keep them warm for 30min~35min to remove the binder, then heat them to 680℃, and then heat them to the brazing temperature of 680℃~800℃ and keep them warm for 5min~20min; finally, cool them to 300℃, and then cool them to room temperature with the furnace to complete the entire brazing process. The entire brazing process is carried out under vacuum.

[0027] Specific implementation method 2: This implementation method is different from the specific implementation method 1 in that the mass fraction of the Ti element in the AgCuInTi solder powder described in step 1 is 3% to 7%. The rest is the same as the specific implementation method 1.

[0028] Specific implementation method 3: This implementation method is different from the specific implementation method 2 in that the AgCuInTi solder powder in step 1 is AgCuInTi3. The rest is the same as the specific implementation method 2.

[0029] Specific embodiment 4: This embodiment is different from specific embodiments 1 to 3 in that the diameter of the diamond particles in step 1 is W7 to W20. The rest is the same as specific embodiments 1 to 3.

[0030] Specific implementation method 5: This implementation method is different from specific implementation method 4 in that the rotation speed of the low-speed ball mill in step 1 is 200 to 300 revolutions per hour. The rest is the same as specific implementation method 4.

[0031] Specific embodiment 6: This embodiment is different from specific embodiment 5 in that the method for pre-treating the graphite and copper base materials described in step 2 is: cutting the two base materials into the required size, polishing the surface of the copper base material to be welded with 600#, 1200#, and 2000# water sandpaper in sequence, polishing the graphite base material with 2000# sandpaper until the surface is flat, placing the polished two base materials in anhydrous ethanol for ultrasonic oscillation for 5min to 10min, and taking them out to dry. The rest is the same as specific embodiment 5.

[0032] Specific implementation method 7: This implementation method is different from specific implementation method 6 in that the binder in step 3 is a 2% by mass hydroxyethyl cellulose aqueous solution. The rest is the same as specific implementation method 6.

[0033] Specific implementation method 8: This implementation method is different from specific implementation method 7 in that the vacuum degree described in step 4 is 6×10 -3 Pa. The rest is the same as the seventh embodiment.

[0034] Specific embodiment 9: This embodiment differs from specific embodiment 8 in that in step 4, the temperature is first raised to 300° C. at 10° C. / min and kept at that temperature for 30 minutes to remove the binder. The rest is the same as specific embodiment 8.

[0035] Specific embodiment 10: This embodiment differs from specific embodiment 9 in that: in step 4, the temperature is raised to 680°C at 10°C / min, then raised to the brazing temperature of 680°C to 800°C at 5°C / min and kept at this temperature for 5min to 20min; finally, the temperature is lowered to 300°C at 5°C / min, and then cooled to room temperature with the furnace to complete the whole brazing process, and the whole brazing process is carried out under vacuum. The rest is the same as specific embodiment 9.

[0036] The present invention is verified by the following tests:

[0037] Experiment 1: This experiment is a method for brazing graphite / copper dissimilar materials using diamond particle reinforced AgCuInTi composite brazing filler metal, which is specifically carried out in the following steps:

[0038] 1. Preparation of composite solder: AgCuInTi solder powder and diamond particles are preliminarily mixed in an agate mortar, and then the mixed powder is placed in a ball mill, and ball milled at a low speed using a ball mill until fully mixed and uniform, to obtain composite solder powder;

[0039] The AgCuInTi solder powder described in step 1 is AgCuInTi3;

[0040] The volume fraction of diamond particles in the composite solder is 10%;

[0041] The particle size of the diamond particles described in step 1 is W7;

[0042] The rotation speed of the low-speed ball mill described in step 1 is 200 rpm;

[0043] 2. Pretreatment of graphite and copper base materials: Cut the two base materials into the required size, polish the surface of the copper base material to be welded with 600#, 1200# and 2000# water sandpaper in turn, and polish the graphite base material with 2000# sandpaper until the surface is smooth. Place the two polished base materials in anhydrous ethanol for ultrasonic oscillation for 5min to 10min, take them out and blow dry;

[0044] 3. Assembling the parts to be welded: mixing the composite solder powder prepared in step 1 with a binder to form a paste solder, applying the paste solder to the surface of the copper base material to be welded by screen printing, and then placing the surface of the graphite base material to be welded on the paste solder, thereby assembling a graphite / diamond particle reinforced AgCuInTi composite solder / copper part to be welded;

[0045] The binder described in step 3 is a 2% by mass aqueous solution of hydroxyethyl cellulose. There is no specific requirement for the amount. The binder is added until it is completely mixed into a paste.

[0046] 4. Brazing: Put the parts to be welded in step 3 into the graphite mold, and then put them into the vacuum furnace. First, heat them to 300℃ at 10℃ / min and keep them warm for 30min to remove the binder, then heat them to 680℃ at 10℃ / min, and then heat them to 740℃ brazing temperature at 5℃ / min and keep them warm for 10min; finally, cool them to 300℃ at 5℃ / min, and then cool them to room temperature with the furnace to complete the whole brazing process. The whole brazing process is carried out under vacuum with a vacuum degree of 6×10 -3 Pa, and the room temperature shear strength of the joint is 23 MPa.

[0047] Figure 1 This is the SEM image of the composite solder powder prepared by ball milling in step 1 of experiment 1. Figure 2 This is the EDS image of the C element in the composite solder powder prepared by the ball milling method in step 1 of experiment 1. The figure shows that the composite solder obtained by the ball milling method is mixed evenly.

[0048] Experiment 2: This experiment is different from Experiment 1 in that the diameter of the diamond particles in step 1 is W20. The rest is the same as Experiment 1. The room temperature shear strength of the joint is finally obtained to be 30 MPa.

[0049] Experiment 3: This experiment differs from Experiment 2 in that the AgCuInTi solder powder in step 1 is AgCuInTi5; the volume fraction of diamond particles in the composite solder in step 1 is 5%. Others are the same as Experiment 2. The room temperature shear strength of the joint is 18 MPa.

[0050] Experiment 4: This experiment differs from Experiment 2 in that the volume fraction of diamond particles in the composite solder described in step 1 is 15%. Others are the same as Experiment 2. The final room temperature shear strength of the joint is 10 MPa.

[0051] Test 5: This test is different from Test 2 in that the brazing temperature in step 4 is 740℃ and kept at this temperature for 5 minutes. The rest is the same as Test 2. The final room temperature shear strength of the joint is 16MPa.

[0052] Test 6: This test is different from Test 2 in that the brazing temperature in step 4 is 740°C and the temperature is kept for 15 minutes. The rest is the same as Test 2. The final room temperature shear strength of the joint is 21 MPa.

[0053] Comparative Test 1: The difference between this test and Test 1 is that no diamond particles are added to the brazing material in step 1, and no ball milling is required; the brazing temperature in step 4 is 780℃ and kept warm for 10 minutes. The rest is the same as Test 1. The room temperature shear strength of the joint finally obtained is 19MPa.

[0054] Figure 3 For comparison, the SEM image of the graphite / copper dissimilar material joint prepared in test 1 is shown below. Figure 4 To compare the XRD patterns of graphite / copper dissimilar material joints prepared in Experiment 1, Figure 5 For comparison, the EDS image of the graphite / copper dissimilar material joint prepared in experiment 1, combined with XRD and EDS, can determine that the weld mainly contains Ag-based solid solution, Cu-based solid solution and Ag-Cu eutectic structure, and a thin TiC reaction layer will be formed on the graphite side of the joint.

[0055] Figure 6 This is the SEM image of the graphite / copper dissimilar material joint prepared in Experiment 2, where 1 and 5 are graphite and copper base materials, 2 is the infiltration layer, 3 is the composite solder layer, and 4 is diamond particles. The structure of the composite solder layer is similar to that of the AgCuInTi3 solder layer, except that diamond particles are evenly distributed in the composite solder layer.

[0056] Comparative Test 2: This test differs from Test 1 in that diamond particles are not added to the brazing material in step 1, and ball milling is not required; the brazing temperature in step 4 is 760°C and kept for 10 minutes. Other conditions are the same as Test 1. The room temperature shear strength of the joint is 15 MPa.

[0057] Comparative test 3: This test is different from test 1 in that no diamond particles are added to the brazing material in step 1, and no ball milling is used; the brazing temperature in step 4 is 740℃ and kept warm for 10 minutes. Other conditions are the same as test 1. The room temperature shear strength of the joint is 17MPa.

Claims

1. A method for brazing graphite / copper dissimilar materials using diamond particle reinforced AgCuInTi composite brazing filler metal, characterized in that The method for brazing graphite / copper dissimilar materials with diamond particle reinforced AgCuInTi composite brazing filler metal is carried out in the following steps:

1. Preparation of composite solder: AgCuInTi solder powder and diamond particles are preliminarily mixed in an agate mortar, and then the mixed powder is placed in a ball mill, and ball milled at a low speed using a ball mill until fully mixed and uniform, to obtain composite solder powder; The volume fraction of diamond particles in the composite solder is 5% to 15%; 2. Pretreatment of graphite and copper base materials; 3. Assembling the parts to be welded: mixing the composite solder powder prepared in step 1 with a binder to form a paste solder, applying the paste solder to the surface of the copper base material to be welded by screen printing, and then placing the surface of the graphite base material to be welded on the paste solder, thereby assembling a graphite / diamond particle reinforced AgCuInTi composite solder / copper part to be welded; 4. Brazing: Place the parts to be welded in step 3 into a graphite mold, and then load them into a vacuum furnace. First, heat them to 300℃~310℃ and keep them warm for 30min~35min to remove the binder, then heat them to 680℃, and then heat them to the brazing temperature of 680℃~800℃ and keep them warm for 5min~20min; finally, cool them to 300℃, and then cool them to room temperature with the furnace to complete the entire brazing process. The entire brazing process is carried out under vacuum.

2. A method for brazing graphite / copper dissimilar materials using diamond particle reinforced AgCuInTi composite brazing filler metal according to claim 1, characterized in that The mass fraction of Ti element in the AgCuInTi solder powder described in step 1 is 3% to 7%.

3. A method for brazing graphite / copper dissimilar materials using diamond particle reinforced AgCuInTi composite brazing filler metal according to claim 2, characterized in that The AgCuInTi solder powder described in step 1 is AgCuInTi3.

4. A method for brazing graphite / copper dissimilar materials using diamond particle reinforced AgCuInTi composite brazing filler metal according to claim 1, characterized in that The particle size of the diamond particles described in step 1 is W7-W20.

5. The method for brazing graphite / copper dissimilar materials using diamond particle reinforced AgCuInTi composite brazing filler metal according to claim 1, characterized in that The rotation speed of the low-speed ball mill described in step 1 is 200 to 300 revolutions per hour.

6. The method for brazing graphite / copper dissimilar materials using diamond particle reinforced AgCuInTi composite brazing filler metal according to claim 1, characterized in that The method for pretreating the graphite and copper base materials described in step 2 is as follows: the two base materials are cut into the required size, the surface of the copper base material to be welded is polished with 600#, 1200#, and 2000# water sandpaper in turn, and the graphite base material is polished with 2000# sandpaper until the surface is smooth, and the two polished base materials are placed in anhydrous ethanol for ultrasonic oscillation for 5min to 10min, and then taken out and blown dry.

7. A method for brazing graphite / copper dissimilar materials using diamond particle reinforced AgCuInTi composite brazing filler metal according to claim 1, characterized in that The binder described in step three is a 2% by mass hydroxyethyl cellulose aqueous solution.

8. The method for brazing graphite / copper dissimilar materials using diamond particle reinforced AgCuInTi composite brazing filler metal according to claim 1, characterized in that The vacuum degree described in step 4 is 6×10 -3 Pa.

9. The method for brazing graphite / copper dissimilar materials using diamond particle reinforced AgCuInTi composite brazing filler metal according to claim 1, characterized in that In step 4, the temperature is first raised to 300°C at 10°C / min and kept at this temperature for 30 minutes to remove the binder.

10. The method for brazing graphite / copper dissimilar materials using diamond particle reinforced AgCuInTi composite brazing filler metal according to claim 1, characterized in that In step 4, the temperature is raised to 680°C at 10°C / min, then raised to the brazing temperature of 680°C to 800°C at 5°C / min and kept at this temperature for 5min to 20min; finally, the temperature is lowered to 300°C at 5°C / min, and then cooled to room temperature with the furnace to complete the entire brazing process. The entire brazing process is carried out under vacuum.

Citation Information

Patent Citations

  • Brazing method for graphite-copper composite commutator

    CN103915745A

  • Solder for brazing red copper and graphite and brazing method

    CN106392367A

  • AgCuTiX alloy foil strip brazing filler metal based on cold spraying process and preparation method thereof

    CN113122837A

  • Active brazing method for improving performance of graphite / copper dissimilar material joint

    CN113478040A

  • Method for brazing connection of AlN ceramic and Cu

    CN113909608A